Efficiency of Technical and Tactical Actions of Greco-Roman Wrestlers (Texas Journal of Multidisciplinary Studies, 2022)
In the article the use of the developed program of distribution of training loads for the development of the sides of preparedness that contributes to the development of technical and tactical preparedness through the selection of various tactical solutions allows to effectively and purposefully manage the training process in the pre-competition period.